2022
DOI: 10.1111/poms.13654
|View full text |Cite
|
Sign up to set email alerts
|

Optimal queue length information disclosure when service quality is uncertain

Abstract: We investigate a server's best queue disclosure strategy in a single‐server service system with an uncertain quality level (which is assumed to be binary). We consider this problem from the perspective of a Bayesian persuasion game. The server first commits to a possibly mixed strategy stating the probability that the queue length will be revealed to customers on their arrival given a realized quality level. The service quality level is then realized, and the server's corresponding queue‐disclosure action is o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…This stream, pioneered by Kamenica and Gentzkow (2011), extensively explores the optimal information policies in diverse settings (see Kamenica, 2019 for a broad review of the literature). The operations management literature has used this framework to explore how a firm or a policymaker optimally disseminates information about inventory and demand (Drakopoulos et al., 2021), queue length/wait times (Lingenbrink and Iyer, 2019; Guo et al., 2022; Anunrojwong et al., 2023), customers’ purchase history (Küçükgül et al., 2022), positions in a schedule (Farahani et al., 2021), and the severity of a disease (Alizamir et al., 2020; de Véricourt et al., 2021). See Candogan (2020) for a comprehensive survey of information design in operations.…”
Section: Related Literaturementioning
confidence: 99%
“…This stream, pioneered by Kamenica and Gentzkow (2011), extensively explores the optimal information policies in diverse settings (see Kamenica, 2019 for a broad review of the literature). The operations management literature has used this framework to explore how a firm or a policymaker optimally disseminates information about inventory and demand (Drakopoulos et al., 2021), queue length/wait times (Lingenbrink and Iyer, 2019; Guo et al., 2022; Anunrojwong et al., 2023), customers’ purchase history (Küçükgül et al., 2022), positions in a schedule (Farahani et al., 2021), and the severity of a disease (Alizamir et al., 2020; de Véricourt et al., 2021). See Candogan (2020) for a comprehensive survey of information design in operations.…”
Section: Related Literaturementioning
confidence: 99%
“…Lingenbrink and Iyer (2019) applied Bayesian persuasion to a queueing setting by considering that the server pre-commits to a queuelength-dependent signaling strategy. Guo et al (2022) showed that under the uncertain service quality, the server can ex ante commit to a quality-dependent queue disclosure strategy before the service quality is realized to persuade more customers to join the system. Different from these studies, we consider a case in which the server has no commitment power and makes the queue disclosure decision after the realization of quality type.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Dobson and Pinker (2006) show that a self-interested firm may hide Production and Operations Management lead time information when customers have a sufficiently low level of heterogeneity in their patience levels. Guo and Zipkin (2007) show that broadcasting more precise information could degrade system performance and customer experience under some waiting cost distributions; therefore, a self-interested firm may intentionally provide incomplete information (Allon et al, 2011;Guo et al, 2022). Dimitrakopoulos et al (2021) study a firm that reveals and hides its QL in alternating periods.…”
Section: Delay Information Provision In Single-service Provider Settingsmentioning
confidence: 99%